A STUDY ON THE INHIBITORY EFFECT OF POLYSACCHARIDES FROM RADIX RANUNCULUS TERNATI ON HUMAN BREAST CANCER MCF-7 CELL LINES - Sun, De-Li; Xie, Han-Bing; Xia, Yun-Zhan (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
The objective of this paper was to study the in vitro anti-breast cancer activity of polysaccharides from Radix ranunculus ternati. Different concentrations of polysaccharide extracts were selected, and MTT assay and flow cytometry (FCM) were used to investigate their growth-inhibitory and apoptosis-inducing effects on human breast cancer MCF-7 cell lines. Radix ranunculus ternati polysaccharides had varying degrees of effects on the growth of human breast cancer MCF-7 cell lines, and the differences were significant compared with the blank control group. FCM showed that the polysaccharides can induce apoptosis. In addition, it can also enhance NK cell activity. Radix ranunculus ternati polysaccharides have a relatively good in vitro anti-breast cancer activity.